Helicobacter pylori serology in autoimmune diseases - Fact or fiction? (2013)
Background: The pathogenesis of autoimmunity is presumed to be a complex process including genetic predisposition, hormonal balance and environmental factors such as infectious agents . Helicobacter pylori , a common bacterial infectious agent has been associated with a variety of autoimmune disorders. However, this bacteria is also thought to play a protective role in the development of multiple sclerosis (MS), systemic lupus erythematosus (SLE) and inflammatory bowel disease (IBD). We tested various links between anti- H. pylori (anti-HP) antibodies and a wide profile of autoimmune diseases and autoantibodies. Methods: A total of 1290 patients diagnosed with 14 different autoimmune diseases from two geographical areas (Europe and Latin America) and two groups of healthy matching controls (n = 385) were screened for the presence of H. pylori IgG antibodies by ' pylori detect ' kit. In parallel, a large profile belonging to three groups of autoantibodies was tested in all sera (anti-nuclear antibodies, autoantibodies associated with thrombophilia and gastrointestinal diseases). Results: Our data demonstrate associations between anti-HP antibodies and anti-phospholipid syndrome, giant cell arteritis, systemic sclerosis and primary biliary cirrhosis. Our data also support a previously known negative association between the prevalence of anti-HP antibodies and IBD. Additionally, links were made between seropositivity to H. pylori and the presence of anti-nuclear antibodies, dsDNA, anti-Ro and some thrombophiliaassociated antibodies, as well as negative associations with gastrointestinal-associated antibodies. Conclusions: Whether these links are epiphenomenal or H. pylori does play a causative role in the autoimmune diseases remains uncertain. The negative associations could possibly support the notion that in susceptible individuals infections may protect from the development of autoimmune diseases.